(untitled) (Altre Modernità, 2016)
This essay outlines the development of the negative hero in Swedish crime literature. While novels from the late nineteenth/early twentieth century novels conceived the villain almost invariably as a foreigner, an alien element to be expelled as soon as possible from the «healthy» Swedish society, in the so-called «social» crime literature started by Sjöwall and Wahlöö in the 1960s and 1970s the criminal was depicted as a victim of society, an average individual driven to crime by the shortcomings of the welfare state. Towards the close of the century this model evolved into the antihero in the style of Lisbeth Salander, a former victim turned avenger, and later still into a more hardened and immoral criminal who commitscrimefor crime’s (and greed’s) sake.